A Methodology for Determining the Proper Point Size for Display Type on Packaging by Means of the Package's Proportions. (December 2014) - Hurley, Rupert Andrew; Fischer, Joanna; Ouzts, Andrew D.; Leininger, John; Thomas, Ronald
<x xml:space="preserve">Abstract</x> The point size of display text on a package was evaluated relative to package proportion with the use of a preference test. This test involved 150 participants examining packaging images showing the product name in various point sizes and being asked their preference. A cascading presentation method modelled after the binary search algorithm was used to determine the exact point size preference for each participant. Participants also completed a survey intended to gather information regarding their motives for their choice. This study was developed to determine the optimal display type size of a package on the basis of its relationship with the package's proportions. It was hypothesized that this proportion would be related to the golden ratio (a ratio of about two‐thirds) that has been suggested to be a particularly aesthetic proportion throughout nature and human history. The results of the study showed that the preferred ratio was actually greater than the golden ratio, equaling 10/12 of the package's width. These results were found to be further influenced by the participant's gender and the packaging structure on which the display type is applied. Although the results are not generalizable to all demographics and products, the methodology used is easily extensible to arbitrary product types. We propose that this methodology for evaluating type size on packages be used by designers as part of the package creation process. Copyright © 2014 John Wiley & Sons, Ltd.